School staff's experiences of supporting pupils from military backgrounds in state schools : A grounded theory exploration. - Biggar, Amy (2021)
Mental health impacts children’s educational experiences (Bowman, McKinstry, Howie & McGorry, 2020). Research shows mental ill-health for military-children is 11% higher than non-military children (Johnson & Ling, 2012). With 170,000 service children in the UK, this is arguably an area of priority research. Military lifestyles afford benefits to military children (Pollock & Van Reken, 2001), but also unique stressors; high mobility and separation from parents are evidenced (Allen & Stanley, 2007; Sogomonyan & Cooper, 2010). Research concerning the unique needs and associated stressors of military children primarily adopts medical or psychological perspectives (Pexton, Farrants & Yule, 2018) and despite being identified as vulnerable (Horten, 2005), military children are largely overlooked by educational researchers (Stites, 2016). Employing a constructivist grounded theory methodology (Charmaz, 2014), this research explores the experiences of school-staff supporting military pupils in mainstream state schools. Data gathering comprised semi-structured interviewing with four school-staff. Data analysis followed processes advocated by Charmaz (2014). Findings were theoretically sensitised through a focused literature review exploring staff confidence and self-efficacy, collective efficacy, Social Cognitive Theory (Bandura, 1986), Ecological Systems Theory (Bronfenbrenner, 1989). Reconceptualization of findings provides new theoretical insights around how school staffs’ perceived confidence and self-efficacy fluctuate under different circumstances and how staff employ strategies in seeming attempts to restore both. This led to the development of the grounded theory: ‘the shift from I-to-we in restoring staff confidence and self-efficacy in a system-of-power versus a system that empowers’. Implications for EP-practice and strategic local authority developments are discussed, highlighting the benefits and challenges of implementing a culture of supervision into school-practice. Further implications also include the need for direct support for school staff, and indirect support for military pupils. The potential benefits of such for the wider school-context are considered. Further reflections highlight the transformative impact of the research journey for the researcher. The potential sources of biases in the research are noted, including ongoing project work in the researcher’s host Local Authority and the researcher’s own assumptions. Accordingly, the ‘theory’ presented can be seen as a localised narrative of wider social processes.